2005
DOI: 10.2174/1568026053507651
|View full text |Cite|
|
Sign up to set email alerts
|

Progress in the Development of Selective Inhibitors of Aurora Kinases

Abstract: Errors in the mitotic process are thought to be one of the principal sources of the genetic instability that hallmarks cancer. Unsurprisingly, many of the proteins that regulate mitosis are aberrantly expressed in tumour cells when compared to their normal counterparts. These may represent a good source of targets for the development of novel anti-cancer agents. The Aurora kinases represent one such family of mitotic regulators. In recent years there has been intense interest in both understanding the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 23 publications
2
63
0
Order By: Relevance
“…In the current study, we explored the possibility that the RNA interference -mediated suppression of Aurora-A could be used as a specific gene-targeting therapy to suppress the progression of ESCC. Moreover, the function of Aurora kinase inhibitors (including the patent literature) has been studied recently, revealing potentially promising anticancer (32,33). Therefore, our results in combination with these findings suggest that taxane-mediated chemotherapy could be more effective in combination with these anti-Aurora agents in ESCC.…”
Section: Discussionsupporting
confidence: 66%
“…In the current study, we explored the possibility that the RNA interference -mediated suppression of Aurora-A could be used as a specific gene-targeting therapy to suppress the progression of ESCC. Moreover, the function of Aurora kinase inhibitors (including the patent literature) has been studied recently, revealing potentially promising anticancer (32,33). Therefore, our results in combination with these findings suggest that taxane-mediated chemotherapy could be more effective in combination with these anti-Aurora agents in ESCC.…”
Section: Discussionsupporting
confidence: 66%
“…Current thought is that overexpression induces centrosome defects, mitotic abnormalities and aneuploidy, which leads to cancer (Meraldi et al, 2004;Giet et al, 2005;Weaver and Cleveland, 2006). Being a putative oncogene, Aurora-A has attracted a great deal of attention as a potential antitumor target (Keen and Taylor, 2004;Mortlock et al, 2005;Naruganahalli et al, 2006). …”
Section: Introductionmentioning
confidence: 99%
“…In earlier publications, a number of quinazoline-based series have been described as Aurora kinase inhibitors [2,22,[42][43][44] . Particularly, the p-benzamidoanilinoquinazoline series was shown to inhibit Aurora A and Aurora B equipotently.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, the p-benzamidoanilinoquinazoline series was shown to inhibit Aurora A and Aurora B equipotently. The investigation of the SAR around the anilino ring linking the key hinge (quinazoline) and the lipophilic pocket (benzamide) binding groups showed that this ring could be replaced with a number of heterocyclic systems to give improvements in both the potency and the physicochemical properties [42] . The linker group also has an important role for the cellular activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation